Long-term resveratrol treatment improves the capillarization in the skeletal muscles of ageing C57BL/6J mice. (2nd January 2021) - Toniolo, Luana; Formoso, Luca; Torelli, Lucio; Crea, Emanuela; Bergamo, Alberta; Sava, Gianni; Giacomello, Emiliana
Abstract: We recently showed that the treatment with Resveratrol (RES) contrasts the effects of ageing on the skeletal muscle (SKM), reduces the appearance of tubular aggregates (TAs), and improves the fatigue resistance. Since fatigue resistance depends on the SKM capillary network, and RES has been described to improve vascularisation, we analysed the SKM capillarization in naturally ageing C57BL/6J male mice, fed with 0.04% RES in the diet for 6 months, which showed a better fatigue resistance in a previous work. Our data show an inverse correlation between the number of capillaries per fibre (CAF) and TAs in both control and treated type IIB fibres, and an increase of CAF in ageing SKM upon RES-treatment. The present work suggests that capillarization is one of the determinants of the development of TAs and fatigue resistance, and that RES can be considered a good candidate to counteract capillary rarefaction in the SKM tissue.